ANALYSIS OF THE IMPROVED T-SHIRT DESIGN OF BALL MILL DRUMS. (Лучшие интеллектуальные исследования, 2025)
Annotation. In this scientific paper, a significant role in the study of the main causes of factors affecting the failure of ball mills is played by the rate of slip on the surfaces of coatings at the expense of the friction forces that occur between the coating and the load current. Changing the slip rate has a major effect on the quality characteristics of the decay processes that determine the decay intensity. A change in the value of a certain pressure mainly only leads to a change in the intensity of  Decay. The decay of Mill drum protectors will have different values depending on the location of the covers. In addition, this article shows the types of ore milling mills operating in hydrometallurgical plants under the Navoi mining and Metallurgical Combine JSC and their share, failure cases and coating failures.